2022
DOI: 10.3390/ijerph19074107
|View full text |Cite
|
Sign up to set email alerts
|

Are You “Nudgeable”? Factors Affecting the Acceptance of Healthy Eating Nudges in a Cafeteria Setting

Abstract: Research has identified nudging as a promising and effective tool to improve healthy eating behavior in a cafeteria setting. However, it remains unclear who is and who is not “nudgeable” (susceptible to nudges). An important influencing factor at the individual level is nudge acceptance. While some progress has been made in determining influences on the acceptance of healthy eating nudges, research on how personal characteristics (such as the perception of social norms) affect nudge acceptance remains scarce. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 53 publications
1
10
2
1
Order By: Relevance
“…Providing social reference points (A3) was least supported. Furthermore, support for nudge types was positively associated with the belief that FS have a role in promoting healthy eating, perceived importance of FV intake, trustworthiness of the choice architect and female gender, broadly in line with previous findings ( 19 , 25 ) . Lastly, support for all types of nudges was positively predicted by perceived effectiveness of each nudge and negatively predicted by perceived intrusiveness above and beyond the contribution of general beliefs about healthy eating and nudging ( 19 , 20 ) .…”
Section: Literature Review and Research Questionssupporting
confidence: 89%
See 1 more Smart Citation
“…Providing social reference points (A3) was least supported. Furthermore, support for nudge types was positively associated with the belief that FS have a role in promoting healthy eating, perceived importance of FV intake, trustworthiness of the choice architect and female gender, broadly in line with previous findings ( 19 , 25 ) . Lastly, support for all types of nudges was positively predicted by perceived effectiveness of each nudge and negatively predicted by perceived intrusiveness above and beyond the contribution of general beliefs about healthy eating and nudging ( 19 , 20 ) .…”
Section: Literature Review and Research Questionssupporting
confidence: 89%
“…We believe that this approach offers more interesting insights than extracting clusters based on their support scores for nudge types. For example, Kawa et al ( 25 ) recently extracted three clusters of German college students based on their support scores for ten nudge tactics derived from MINDSPACE typology ( 14 ) , via a k-means non-hierarchical cluster analysis. While Kawa et al 's identification of three clusters (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Or should the expected efficacy be a more relevant criteria, regardless of the manipulative nature of the intervention? Being nudges mediated by 'System 1heuristics, if there is a well-known disapproval of more intrusive measures (hence relying more on System 1), their application taps directly into the concerns of the critics about preserving citizens' deliberate choices [14].…”
Section: Discussionmentioning
confidence: 99%
“…A series of landmark studies [12] found that gain-framed messages worked better in prevention behavior, whereas loss-framed messages encouraged detection behavior. According to the taxonomy proposed by Thaler and Sunstein [6], social norm information also tends to encourage desired health behavior, especially when combined with other techniques [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…It has been applied to various fields as a method to influence people's behavioral decisions. Examples include influencing consumers' dietary decisions [9,10], encouraging investors to implement sustainable and responsible investment decisions [11,12], promoting students' self-directed learning educational decisions [13,14], reducing social media users' misinformation sharing decisions [15][16][17], and changing individuals' pro-social behavior decisions [18][19][20].…”
Section: Introductionmentioning
confidence: 99%